FAKTOR-FAKTOR KETERLAMBATAN PROYEK JALAN RAYA DI KOTA KUPANG BERDASARKAN PERSEPSI STAKEHOLDER - Ramang, Ruslan; Frans, John H.; Djahamouw, Putri D. K. (Jurnal Teknik Sipil, 2017)
Development of road infrastructure in Kupang city today has been a concern and the priority of the government in order to support the acceleration of the economy in the Kupang city.However, the problems that occurred in the project implementation is incomplete highway projects in a timely, cost and quality that has been set.The purpose of this study was to determine the weighting of the factors that cause delays in the completion of a highway project according to perception of stakeholder and a model of the delay in the completion of a highway project in Kupang city.Data analysis technique using Microsoft Excelto obtain a weighting of the delay factors of each respondents, andusing Factor Analysis method to obtain the model of delay factors. From the results of analysis show that the main factor causing the delay of highway project in Kupang city according to respondents of contractor is a delay provision of heavy equipment factor with a percentage of 4.64%, then according to respondents of consultant is design error factor with a percentage of 4.81%, and then according to respondents of Dinas PU is scarcity of material required with a percentage of 4.53%. The result gained models of delays interpreted that project management factors ( F1) provide the most impact on delay in the completion of a highway project in Kupang city that is equal to 13.187%.